Society for Birth Defects Research and Prevention 2022–2027 strategic plan. Issue 7 (1st March 2023) - Makris, Susan L.; Beyer, Bruce K.; DeLise, Anthony; Williams, Amy L.; Roberts, Linda G.; Hardy, Janet R.; Robinson, Joshua F.; Feldkamp, Marcia L.
Abstract: Background: The sixth Strategic Planning Session of the Society for Birth Defects Research and Prevention (BDRP) was held on April 24–25, 2022, in Alexandria, VA. Methods: This effort built upon previous strategic planning sessions, conducted every 5 years. Results: The overall process was designed to identify BDRP's vision, purpose, culture, and potential, as well as to communicate the value that BDRP brings to its members, volunteers, partners, and the greater community. Conclusions: The BDRP 2022–2027 Strategic Plan provides the BDRP leadership, members, and staff with a clearly articulated framework and direction to support long‐term sustainability and growth of the society.